2016
DOI: 10.1016/j.scitotenv.2016.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of precipitation input for SWAT modeling in Alpine catchment: A case study in the Adige river basin (Italy)

Abstract: Precipitation is often the most important input data in hydrological models when simulating streamflow. The Soil and Water Assessment Tool (SWAT), a widely used hydrological model, only makes use of data from one precipitation gauge station that is nearest to the centroid of each subbasin, which is eventually corrected using the elevation band method. This leads in general to inaccurate representation of subbasin precipitation input data, particularly in catchments with complex topography. To investigate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
156
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(167 citation statements)
references
References 70 publications
9
156
0
2
Order By: Relevance
“…The CHIRPS data resulted in 'satisfactory' simulations of the stream flow [26]. However, the TRMM data set was associated with 'unsatisfactory' model performance by Tuo et al [26]. In the current work, TRMM and CHIRPS data were ranked at 16th and 17th, respectively, indicating poor overall model performance relative to the other MAP methods tested.…”
Section: Calibrated Model Performancementioning
confidence: 57%
See 3 more Smart Citations
“…The CHIRPS data resulted in 'satisfactory' simulations of the stream flow [26]. However, the TRMM data set was associated with 'unsatisfactory' model performance by Tuo et al [26]. In the current work, TRMM and CHIRPS data were ranked at 16th and 17th, respectively, indicating poor overall model performance relative to the other MAP methods tested.…”
Section: Calibrated Model Performancementioning
confidence: 57%
“…When calibrated SWAT model performance was ranked, the IDW_2 method performed best overall (i.e., all time steps tested were considered) ( Table 8). The IDW_2 method has also been shown to work well in other locations with considerably different climate and physiographic characteristics compared to the study catchment [4,17,26]. For example, Tuo et al [26] showed that the IDW method was the most accurate method tested for SWAT model precipitation input on SWAT simulated stream flow in an alpine Aldige river basin of north-eastern Italy.…”
Section: Calibrated Model Performancementioning
confidence: 94%
See 2 more Smart Citations
“…For instance, CHIRPS has been Water 2017, 9, 615 4 of 17 used to quantify the impact of decreasing precipitation trends and increasing temperatures trends in the Greater Horn in Africa [22], and it validated using the data from 21 ground stations in Northeast Brazil [23]. CHIRPS dataset has also been used it to obtain a comprehensive evaluation of eight high spatial resolution precipitation products in an Alpine catchment, the Adige Basin in Italy [24], and to validate a hydrological model to simulate stream flow in a complex topography [25]. Additionally, the same database was successfully used for the analysis of precipitation extremes over Cyprus [26] and Bhutan [27].…”
Section: Precipitation Datasetmentioning
confidence: 99%